Diagnosis of autism spectrum disorders in 2‐year‐olds: a study of community practice. (20th August 2012) - Corsello, Christina M.; Akshoomoff, Natacha; Stahmer, Aubyn C.
Abstract : Background:  Longitudinal research studies have demonstrated that experienced clinicians using standardized assessment measures can make a reliable diagnosis of autism spectrum disorders (ASDs) in children under age 3. Limited data are available regarding the sensitivity and specificity of these measures in community settings. The aims of this study were to determine how well a standardized diagnostic observational measure (Autism Diagnostic Observation Schedule – ADOS) functions alone, and with a brief parent measure within a community setting when administered by community clinicians. Methods:  Clinical records for 138 children between the ages of 24 and 36 months of age who were evaluated for possible ASD or social/language concerns at a hospital‐based developmental evaluation clinic were examined. Evaluations were conducted by community‐based clinical psychologists. Classification results obtained from standardized diagnostic measures were compared with case reviewer diagnosis, by reviewers blind to scores on diagnostic measures, using The Records‐based Methodology for ASD Case Definition that was developed by the Metropolitan Atlanta Developmental Disabilities Surveillance Program. Results:  When compared with case review diagnosis, the ADOS demonstrated strong sensitivity and specificity for both Autism versus Not Autism and ASD versus Nonspectrum (NS) diagnoses in this young sample. The Social Communication Questionnaire (SCQ), using the lower cutoff of ≥12, had adequate sensitivity when differentiating Autism from Not Autism, but weak sensitivity when differentiating ASD from NS, missing about 80% of the children with pervasive developmental disorder – not otherwise specified. Using either the Modified Checklist for Autism in Toddlers or the SCQ in combination with the ADOS did not result in improved specificity over the ADOS alone and led to a drop in sensitivity when differentiating ASD from NS disorders. Conclusions:  These results demonstrate that following best practice guidelines, the ADOS can be successfully incorporated into clinical practice with relatively good sensitivity and specificity, and worked well with a referred sample of 2‐year‐olds. A parent questionnaire did not lead to any improvement in diagnostic classification above the ADOS used in isolation.